1995
DOI: 10.1097/00000542-199508000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Determinants of Early Postoperative Oxygen Consumption in Elderly Patients

Abstract: The metabolic demands associated with postoperative shivering in elderly patients are less than those reported previously in younger persons. These findings suggest that if hypothermia predisposes to cardiovascular complications in the postoperative period, these complications are not likely to be mediated by shivering and increased metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(22 citation statements)
references
References 33 publications
0
20
0
2
Order By: Relevance
“…Reduced temperature in the immediate postoperative period can be advantageous in cardiac surgery patients, because oxygen consumption is directly related to temperature. 23 However, Chaney and colleagues showed that methylprednisolone had no clinical bene®ts in patients undergoing elective CABG and possibly hindered early postoperative tracheal extubation. 24 This contrasts with our ®nding that the dexamethasone-treated patients were extubated earlier than the control patients (albeit statistically insigni®cant).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced temperature in the immediate postoperative period can be advantageous in cardiac surgery patients, because oxygen consumption is directly related to temperature. 23 However, Chaney and colleagues showed that methylprednisolone had no clinical bene®ts in patients undergoing elective CABG and possibly hindered early postoperative tracheal extubation. 24 This contrasts with our ®nding that the dexamethasone-treated patients were extubated earlier than the control patients (albeit statistically insigni®cant).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia frequently occurs during anaesthesia and surgery; this has been shown to be associated with adverse clinical outcomes including postoperative shivering [1], increased blood loss [2], decreased drug metabolism and clearance [3], postoperative myocardial ischaemia [4], wound infection [5] and delayed recovery from anaesthesia [6]. Hypothermia results largely from an internal core‐to‐peripheral redistribution of body heat [7].…”
mentioning
confidence: 99%
“…Also another study reported no significant difference between ketamine and pethidine in controlling postoperative shivering; however, pethidine is the medication of choice due to the high incidence of side effects in the ketamine group (17, 18). In a similar study, no case of shivering was reported in the pethidine group.…”
Section: Discussionmentioning
confidence: 99%